Computational analysis of PTP-1B site-directed mutations and their structural binding to potential inhibitors: Analysis of PTP-1B site-directed mutations - Tasleem, Munazzah; Shoaib, Ambreen; Al-Shammary, Asma; Abdelgadir, Abdelmuhsin; Alsamar, Zeina; Jamal, Qazi Mohammad Sajid; Alrehaily, Abdulwahed; Bardcki, Fevzi; Sulieman, Abdel Moneim E.; Upadhyay, Tarun Kumar; Ansari, Irfan Ahmad; Lai, Dakun; et al. (Cellular and Molecular Biology, 2022)
Protein tyrosine phosphatase-1B (PTP-1B) is a well-known therapeutic target for diabetes and obesity as it suppresses insulin and leptin signaling. PTP-1B deletion or pharmacological suppression boosted glucose homeostasis and insulin signaling without altering hepatic fat storage. Inhibitors of PTP-1B may be useful in the treatment of type 2 diabetes, and shikonin, a naturally occurring naphthoquinone dye pigment, is reported to inhibit PTP-1B and possess antidiabetic properties. Since the cell contains a large number of phosphatases, PTP-1B inhibitors must be effective and selective. To explore more about the mechanism underlying the inhibitor’s efficacy and selectivity, we investigated its top four pharmacophores and used site-directed mutagenesis to insert amino acid mutations into PTP-1B as an extension of our previous study where we identified 4 pharmacophores of shikonin. The study aimed to examine the site-directed mutations like R24Y, S215E, and S216C influence the binding of shikonin pharmacophores, which act as selective inhibitors of PTP-1B. To achieve this purpose, docking and molecular dynamics simulations of wild-type (WT) and mutant PTP-1B with antidiabetic compounds were undertaken. The simulation results revealed that site-directed mutations can change the hydrogen bond and hydrophobic interactions between shikonin pharmacophores and many residues in PTP-1B’s active site, influencing the drug’s binding affinity. These findings could aid researchers in better understanding PTP-1B inhibitors’ selective binding mechanism and pave the path for the creation of effective PTP-1B inhibitors.